2016
DOI: 10.1016/j.ajpath.2015.09.005
|View full text |Cite
|
Sign up to set email alerts
|

S100A8 and S100A9 Are Induced by Decreased Hydration in the Epidermis and Promote Fibroblast Activation and Fibrosis in the Dermis

Abstract: The most critical function of the epidermis is to prevent water loss and maintain skin homeostasis. Disruption of the functional skin barrier causes delayed wound healing, hypertrophic scarring, and many skin diseases. Herein, we show that reduced hydration increases the expression of S100 protein family members, S100A8/S100A9, in stratified keratinocyte culture and human ex vivo skin culture. Immunohistological analyses show that S100A8/A9 are highly expressed in the epidermis of human hypertrophic scar and k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 54 publications
4
56
0
Order By: Relevance
“…S100a8 is an inflammatory marker in various diseases. A recent study demonstrated that S100A8 deficiency impaired keratinocyte migration and proliferation . In the present study, IL‐6, TNF‐α, CCL2 and s100a8 mRNA expression was downregulated in the wound site of NALP3‐KO mice.…”
Section: Discussionsupporting
confidence: 64%
“…S100a8 is an inflammatory marker in various diseases. A recent study demonstrated that S100A8 deficiency impaired keratinocyte migration and proliferation . In the present study, IL‐6, TNF‐α, CCL2 and s100a8 mRNA expression was downregulated in the wound site of NALP3‐KO mice.…”
Section: Discussionsupporting
confidence: 64%
“…S100A9, which is a downstream gene of Na x , functions as a pro‐inflammatory cytokine in the epidermis . We observed that S100A9 is highly expressed in the epidermis of human hypertrophic scars and keloid tissues in which the barrier function of the skin is impaired . Increased expression of S100A9 has also been detected in psoriatic skin lesions .…”
Section: Resultsmentioning
confidence: 68%
“…We previously showed that Na x controls pro‐inflammatory signalling in the epidermis . S100A9, which is a downstream gene of Na x , functions as a pro‐inflammatory cytokine in the epidermis . We observed that S100A9 is highly expressed in the epidermis of human hypertrophic scars and keloid tissues in which the barrier function of the skin is impaired .…”
Section: Resultsmentioning
confidence: 84%
“…The knockdown of keratinocyte S100A8 , recently shown to be upregulated in both keloid and hypertrophic scar epidermis, resulted in a failure to activate co-cultured fibroblasts and reduction in dermal fibrosis [48]. As a mediator of neutrophil migration [49, 50], S100A8 is found in the supra-basal epidermis following injury, but gradually returns to baseline in a normally healed wound [51].…”
Section: Resultsmentioning
confidence: 99%